Estimation of crossbreeding and genetic parameters for reproductive traits of Boer x Central Highland goats in Ethiopia. - Zeleke Tesema; Belay Deribe; Mekonnen Tilahun; Alemu Kefale; Getachew Worku Alebachew; Kefyalew Alemayehu; Tesfaye Getachew; Damitie Kebede; Mengistie Taye; Solomon Gizaw (PLoS ONE)
Additive genetic and non-additive parameters for reproductive traits of Boer x Central Highland goats were estimated. Pedigree and performance records comprised of Central Highland and their crosses with Boer goats were collected from 2009 to 2018 in the Sirinka Agricultural Research Center sheep and goat breeding station. Least-squares means for genotypes were obtained using a general linear model procedure in SAS. To estimate crossbreeding parameters, breed additive, heterotic, and recombination effects were fitted as fixed covariates instead of genotypes. Variance, heritability, and repeatability estimates were estimated through the AI-REML algorithm using WOMBAT software. Genotype did not significantly (P>0.05) influence most of the reproductive traits studied except for gestation length. The additive effect for litter size at birth (LSB), total litter birth weight (LBW), total litter weaning weight (LWW), litter size at weaning (LSW), and gestation length (GL) was estimated to be -0.004 kid, 0.08 kg, -3.18 kg, -0.54 kid, and 3.69 days, respectively. The contribution of heterosis to LSB, LWW, and GL of crossbred goats was negative, while the estimates for LBW and LSW were positive. However, Boer goats' heterosis effect and direct additive contribution to reproductive traits were insignificant (P>0.05) except for LSW. The recombination effect was negligible and not significant (P>0.05) for all traits examined. The direct heritability estimate for LSB, LWB, LWW, LSW, and GL were 0.050, 0.098, 0.086, 0.018, and 0.00, respectively. The repeatability estimates for LSB, LWB, LWW, LSW, and GL were 0.149, 0.116, 0.099, 0.086, and 0.061, respectively. The result indicates that improvement in reproductive traits would not be expected by crossing Boer with Central Highland goats. In addition, heritability estimates indicate that the improvement of reproductive traits through selection will be small, and the repeatability estimates indicate that multiple records have to be used to make a decision of culling or selection.